Role of Budgeting in Modern Corporate Governance (Empirical Study in the Czech Republic) - Jana Fibírová; Libuše Šoljaková (European Financial and Accounting Journal, 2009)
The differing opinions of both experts and managers on the application of budgets in the dynamic changing business environment were inspiration for the empirical study that is oriented on the importance of budgets to performance management. The paper results from the empirical research. Analyses and conclusions presented in this paper cover the following issue: The first part analyses changes in the application of budgets in recent years and the indicators of these changes. The second part is oriented on the opinions of managers of budgets and explores whether managers consider budgets an important management tool supporting and improving Corporate Governance. Analyses concentrate also on differences between the attitudes of financial and nonfinancial managers and between middle level and top managers. The last part of the project focuses on recognition of factors that have an influence on budget consideration such as methods of budget preparation, manager participation in budgeting process, level of power and responsibility managers, relation to incentive scheme, and the personal characteristics of managers.
Keywords: M41; 650; Budgeting; Corporate Governance; Management Tools